Perancangan User Experience Website Chawaty menggunakan Pendekatan Human-Centered Design (HCD) - Alifia Wahyu Sektyawardani; Hanifah Muslimah Az-Zahra; Bondan Sapta Prakoso (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
CV PERDU LA is a Chawaty SME business entity located in Surabaya City, East Java, and has been established in 2012. The Covid-19 pandemic has caused Chawaty to experience a very significant decline in turnover. Thus increasing accuracy and speed in responding to the current pandemic conditions, CV PERDULA seeks to provide website-based services whose aim is to make it easier for potential consumers who want to know what products are offered along with product specifications and advantages. Produce useful services by involving humans, namely users and stakeholders to meet the satisfaction and needs of using the Chawaty website. The stages used in the HCD approach are the process of specifying the context of use and user needs through an interview process with stakeholders from Chawaty and users who use the service, then the process of making wireframe, wireflow, and high-fidelity prototype designs based on identified design guidelines. previously. The design solution design in the form of a high-fidelity prototype is the final result of the design process, which is then carried out by an evaluation process using the user experience questionnaire method. The results of the evaluation process get positive scores on every scale and aspect of UEQ. The attractiveness scale has a value of 2,205, the clarity scale is 2,086, the efficiency scale is 2,321, the accuracy scale is 2,214, the stimulation scale is 2,393, and the novelty scale is 2,093. The UEQ benchmark chart gets the excellent category on each scale.